Analysis of the Influence of Social Media Marketing Activities on Purchase Intention with Brand Equity Mediation on Korean Merchandise - Edy Yulianto Putra; Tasya (International Journal of Social Science and Religion (IJSSR), 2023)
This study aims to analyze and identify the factors influencing purchase intention in Korean merchandise with the mediation of brand equity. The object of this study is to respondents aged 15-26 years and the average is still in school and already working who intend to buy Korean merchandise. The independent variables used in this study are entertainment, interaction, trendiness, advertisement, and e-wom, as well as brand equity as an intervening variable and purchase intention as a dependent variable. This study was obtained using a questionnaire filling method, a quantitative approach, and a purposive sampling technique. The author used Smart PLS to analyze the data.